African Human Rights Law Reports 2010 - Edited by The African Commission on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria (Pretoria University Law Press (PULP), 2013)
African Human Rights Law Reports 2010 Edited by The African Commission on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria 2013 ISSN: 1812-2418 Pages: xxxi 239 Print version: Available Electronic version: Free PDF available